FACTORS AFFECTING INWARD FOREIGN DIRECT INVESTMENT: CASE OF ASEAN COUNTRIES - Grace, Gabriela (JURNAL INFO ARTHA, 2019)
The goal of this study is to identify the determinants of foreign direct investment in members of ASEAN countries (will be known as ASEAN-9 and ASEAN-7 from 1990 to 2017 by using Pooled Least Square as the model.The results show that market size, trade openness, infrastructure, research & development, and inflation have positive effects on inward FDI which can be considered as determinants of FDI. On the other hand, human capital and real interest rates show a negative sign.This study also discussed the FDI trend after the global finance crisis in 2008. The results indicate that the annual trend for FDI after 2008 is positive, which means there is no big impact from the global financial crisis of 2008 on FDI inflows.Based on the results, GDP, infrastructures, and trade openness become the important factors to attract foreign investors. Therefore, government can improve through policies, such as easing trade procedures, or improving the quantity and quality of the infrastructure.The difference finding is found on the negative result of human capital effect on inward FDI. Thus, the quality of human resources still needs improvement because it can improve thelow-tech into high-tech destination countries for FDI.